Outcomes of Open Cystolithotomy and Percutaneous Cystolithotripsy in the Management of Urinary Bladder Stone - Shrestha, Naresh Man (Journal of Nepalgunj Medical College, 2022)
Introduction: Urinary bladder stone occupies only 5% of all urinary tract stone. Various techniques have been used for the management of bladder stone. Open Cystolithotomy is the traditional treatment but a percutaneous approach has been also in practice. Aims: To confirm the best options between open cystolithotomy and percutaneous cystolithotripsy for the treatment of bladder stone. Methods: It is a prospective hospital based study from May 2019 to January 2021 in Nepalgunj Medical College. Total 42 patients with inclusion criteria were divided into two groups. Group I was allocated to 21 patients who were treated with open cystolithotomy while Group II were allocated to 21 patients who were treated with percutaneous cystolithotripsy. Two groups were compared for stone free rate, mean hospital stay, mean postoperative scar, mean operation time and rate of post-operative complications. Results: The stone free rate in Group I was 100 % and in Group II was 90.47 %. Mean Operation time was in Group I and Group II were 40.09+ 2.48 minutes and 31.38+15.65 days, respectively with p<0.05. Mean hospital stay was significantly low in Group II (3.71+1.87 days ) when compared to Group I (7.67+ 2.12 days) with p<0.001. Mean scar length of Group I (5.466+2.9 cm) with respect to Group II (1.04+0.09) was significantly long (p<0.01). Rate of complications were not significantly different between two groups (p>0.5). Conclusion: For management of urinary bladder stones sized up to 4 cm, both open cystolithotomy and percutaneous cystolithotripsy are effective, with a low incidence of complications. However, comparing the surgery time, hospital stay, length of scar between two procedures, percutaneous cystolithotripsy procedure is more beneficial for treatment of urinary bladder stone.